Eye Movement Desensitization and Reprocessing in adolescents with autism; Efficacy on ASD symptoms and stress - Leuning, Esther Marion; van den Berk-Smeekens, Iris; van Dongen-Boomsma, Martine; Staal, Wouter G. (Frontiers in Psychiatry, 2023)
Abstract Eye Movement Desensitization and Reprocessing (EMDR) is a well-established and thoroughly researched, treatment method for posttraumatic stress symptoms. When patients with an autism spectrum disorder (ASD) are treated with EMDR for their Posttraumatic Stress Disorder (PTSD), they may sometimes experience a decrease in the core symptoms of ASD. This explorative pre-post design study is designed to test whether EMDR with a focus on daily experienced stress, is effective in reducing ASD symptoms and stress in adolescents with ASD. Twenty-one adolescents with ASD (age 12 to 19) were treated with ten sessions EMDR, focusing on events of daily experienced stress. No significant decrease of ASD symptoms was found on the total score of the Social Responsiveness Scale (SRS) as reported by caregivers from baseline to end measurement. However, there was a significant decrease on total caregivers SRS score comparing the baseline to the follow-up measurement. On two subscales, Social Awareness and Social Communication, a significant decrease was found from baseline to follow-up measurement. On the subscales Social Motivation and Restricted Interests and Repetitive Behavior, no significant effects were found. On pre- and posttest scores of total ASD symptoms measured by the Autism Diagnostic Observation Schedule (ADOS-2), no significant effects were found. On the contrary, scores on self-reported Perceived Stress Scale (PSS) showed a significant decrease from baseline to follow-up measurement. Also, 52% of adolescents showed a significant clinical improvement at endpoint measurement on the Clinical Global Impression Scale, rated by an independent child psychiatrist. In sum, the results suggest a partial effect of EMDR in adolescents with ASD on ASD symptoms, rated by their caregivers. In addition, the results of this study show that EMDR treatment on daily experienced stress significantly reduce perceived stress as reported by the participants, and show an improved global clinical functioning. The results also suggest a ‘sleeper effect’, where no significant effects were found between baseline- and post- measurements, but only between baseline- and follow up measurement three months after treatment. This finding is in line with other studies investigating psychotherapeutic effects in ASD. Implications for clinical practice and suggestions for future research are discussed.